2021
DOI: 10.3389/fbioe.2021.603408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Mechanical Environment on the Regeneration of Osteochondral Defects

Abstract: Articular cartilage is a highly specialised connective tissue of diarthrodial joints which provides a smooth, lubricated surface for joint articulation and plays a crucial role in the transmission of loads. In vivo cartilage is subjected to mechanical stimuli that are essential for cartilage development and the maintenance of a chondrocytic phenotype. Cartilage damage caused by traumatic injuries, ageing, or degradative diseases leads to impaired loading resistance and progressive degeneration of both the arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 276 publications
2
55
0
Order By: Relevance
“…Scientists have been researching the role of different materials in the treatment of osteochondral lesions for many years. The properties of the materials can greatly influence of the mechanical environment of the healing process in treatment osteochondral defects (Davis et al, 2021). It is possible to study various implants on the experimental animal models under physiological conditions, as they provide better understanding of the response in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have been researching the role of different materials in the treatment of osteochondral lesions for many years. The properties of the materials can greatly influence of the mechanical environment of the healing process in treatment osteochondral defects (Davis et al, 2021). It is possible to study various implants on the experimental animal models under physiological conditions, as they provide better understanding of the response in humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, overloading conditions in joints, such as excessive sport, obesity, and trauma, may increase pro-inflammatory cytokines, reduce Col II and aggrecan (AGG), and even chondrocyte apoptosis. Therefore, it is essential to establish a proper loading condition to facilitate cartilage regeneration [ 147 ].…”
Section: Articular Cartilage Regeneration Under Abnormal Conditionsmentioning
confidence: 99%
“…Promoting proliferation and transmission of biochemical signals (only when biofunctionalization with adhesion ligands [83]) [94] Biomaterials for tissue engineering should be biodegradable, have a controlled chemical composition and have a porosity to allow optimal cell adhesion, migration, and production of endogenous ECM components [20,[95][96][97]. Another important characteristic of the scaffold is stiffness, that is, the ability to resist mechanical deformation [98,99].…”
Section: Collagenmentioning
confidence: 99%
“…Another important characteristic of the scaffold is stiffness, that is, the ability to resist mechanical deformation [98,99]. Engler et al were the first to explore the effect of the scaffold stiffness parameter on MSCs and showed that stiff substrates promote the development of a highly organized cytoskeleton with a fusiform morphology, while soft substrates promote the development of a rounded chondrocyte-like morphology and enhanced expression of chondrogenic markers [96].…”
Section: Collagenmentioning
confidence: 99%